Prenatal exposure to polychlorinated biphenyls and asthma, eczema/hay fever, and frequent ear infections. (3rd October 2018) - Parker-Lalomio, Margaret; McCann, Kenneth; Piorkowski, Julie; Freels, Sally; Persky, Victoria W.
ABSTRACT: Objectives: The effects of prenatal exposure to Polychlorinated biphenyls (PCBs) on the development of asthma, frequent ear infections, and eczema/hay fever are not well understood. We aim to investigate associations between prenatal PCB exposure and these health outcomes in the offspring of women who worked at the LaSalle Electrical Utilities Company (EUC). Methods: A retrospective cohort with at least one live birth and known employment time at EUC was eligible for this analysis. Exposure was defined and categorized by the number of fiscal quarters worked during the PCB era (1952–1981). A total of 288 women with 800 live births were included. A Chi-Square test was used to compare maternal and child characteristics across exposure groups and repeated measures logistic regression, controlling for clustering among siblings, was used to assess the associations between prenatal PCB exposure and these outcomes. Results: After adjustment for confounding and independent maternal predictors, 1–4 quarters of prenatal exposure to PCBs increased the odds for asthma (OR 3.24[1.30–8.09]), eczema/hay fever (OR 3.29[1.54–7.04]), and frequent ear infections (OR 2.24[1.19–4.22]) when compared with persons unexposed/exposed only to naphthalenes. The significance of the associations varied by exposure period and level of exposure, with the strongest associations in those employed exclusively after 1952 when PCBs were introduced. Conclusions: These results support previous findings of associations of prenatal exposure to PCBs with asthma, eczema/hay fever, and frequent ear infections. Additional prospective studies are needed to confirm these findings. Also required are more precise PCB exposures to separate them from other exposures in occupational settings.